Vitellogenin dipstick: rapid detection of sexual maturity in catfish species for shariah compliant aquaculture innovation - Othman, Roshani; Suliman, Nur Akmal; Mansor, Farrah Nazuha; Mohd Zan, Mohd Syahril; A Ghani, Intan Faraha; Abdul Haq Hazman, Sulaiman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The sustainability and ethical progress of aquaculture is highly dependent on accurate, non-invasive tools to monitor the reproductive maturity of broodstock. The aim of this study was to develop and evaluate a vitellogenin dipstick, a lateral flow immunoassay for the rapid detection of vitellogenin (Vtg), a biomarker of sexual maturity, in female catfish to support Shariah-compliant aquaculture practises. Polyclonal antibodies were generated in rabbits using purified Vtg from Hemibagrus nemurus selected for its high Vtg expression. These antibodies were conjugated to gold nanoparticles and applied to nitrocellulose membranes to develop a field applicable dipstick. Plasma samples were collected from four catfish species, Clarias gariepinus (mature and immature), Pangasius pangasius, Hemibagrus wyckiodes and H. nemurus, and analysed in triplicate. The Vtg content was quantified by dipstick and competitive ELISA using optimised antibody dilutions of 1:500 to 1:8000 and standard Vtg concentrations of 125–500 ng/mL. SDS-PAGE confirmed the presence of Vtg bands (95–175 kDa) in females and the absence in males. Notably, H. nemurus had the highest concentration of Vtg in plasma (84.040 ± 5.33 mg/mL), while C. gariepinus (mature) had the lowest (8.539 ± 2.68 mg/mL). The Vtg dipstick showed high sensitivity by detecting Vtg in concentrations of up to 50 ng/mL within 10 minutes and showed a strong correlation with the ELISA and the gonadosomatic index (r = 0.87). The developed test strip is portable, cost-effective (<RM 5 per test) and eliminates the need for synthetic hormones, providing a humane and Shariah-compliant solution for aquaculture. In conclusion, the Vtg dipstick is a promising innovation for non-invasive monitoring of catfish reproduction that supports ethical breeding decisions and contributes to sustainable aquaculture practises.